The novel human HUEL (C4orf1) protein shares homology with the DNA-binding domain of the XPA DNA repair protein and displays nuclear translocation in a cell cycle-dependent manner - Sim, D.L.C. (2012)
10.1016/S1357-2725(01)00156-X